Veterans with Traumatic Brain Injury–related Ocular Injury and Vision Dysfunction: Recommendations for Rehabilitation. Issue 1 (January 2022) - Winkler, Sandra L.; Finch, Dezon; Wang, Xinping; Toyinbo, Peter; Marszalek, Jacob; Rakoczy, Chrystyna M.; Rice, Candice E.; Pollard, Kendra; Rhodes, Matthew A.; Eldred, Kia; Llanos, Imelda; Peterson, Michael; et al.
Abstract : SIGNIFICANCE: We know the prevalence of traumatic brain injury (TBI)–related vision impairment and ocular injury symptoms. Lacking is an understanding of health care utilization to treat these symptoms. Utilization knowledge is important to structuring access to treatment, identifying clinical training needs, and providing evidence of the effectiveness of treatment. PURPOSE: This article reports rehabilitation, glasses/contacts, and imaging/photography/video recommendations made by optometrists and ophthalmologists as part of the Department of Veterans Affairs–mandated Performance of Traumatic Brain Injury Specific Ocular Health and Visual Functioning Examination administered to veterans with TBI at Department of Veterans Affairs polytrauma specialty facilities. METHODS: Using a retrospective design, natural language processing, and descriptive and regression statistics, data were analyzed for 2458 Operation Enduring Freedom/Operation Iraqi Freedom veterans who were administered the mandated examination between 2008 and 2017. RESULTS: Of the 2458 veterans, vision rehabilitation was recommended for 24%, glasses/contacts were recommended for 57%, and further imaging/photography/video testing was recommended for 58%. Using key words in the referral, we determined that 37% of veterans were referred to blind rehabilitation, 16% to occupational therapy, and 3% to low-vision clinics. More than 50% of the referrals could have been treated by blind rehabilitation, occupational therapy, or low-vision clinics. Rehabilitation referrals were significantly associated with younger age, floaters, photosensitivity, double vision, visual field and balance deficits, dizziness, and difficulty reading. In comparison, prescriptions for glasses and contacts were associated with older age, photosensitivity, blurred vision, decreased visual field and night vision, difficulty reading, and dry eye. Imaging/photography/video testing was associated with floaters, photosensitivity, and headache. CONCLUSIONS: Findings delineate service delivery models available to veterans with TBI-related vision impairment. The challenge these data address is the lack of clear paths from diagnosis of TBI to identification of vision dysfunction deficits to specialized vision rehabilitation, and finally to community reintegration and community based-vision rehabilitation.